2005
DOI: 10.1007/s11663-005-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of carbon from coal-chars into liquid iron at 1550 °C

Abstract: Carbon-dissolution studies were carried out on four coal-chars (ash content ranging from 9.04 to 12.61 wt pct), using the carburizer-cover method, and the rates of carbon transfer into liquid iron at 1550°C were determined. A theoretical model was developed for estimating the interfacial area of contact between the chars and the liquid iron. Using a force-balance approach, the partial penetration of the particles was calculated numerically and the total solid/liquid contact area was evaluated for a range of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 22 publications
3
43
1
Order By: Relevance
“…In stage II the appearance of a denser CA layer formed reduced the contact between the coke and liquid iron slowing the kinetics. These findings were broadly consistent with what had been previously reported in the literature [7][8][9][10][11][12][13] but the information on the mineral structures formed was new.…”
Section: Introductionsupporting
confidence: 91%
“…In stage II the appearance of a denser CA layer formed reduced the contact between the coke and liquid iron slowing the kinetics. These findings were broadly consistent with what had been previously reported in the literature [7][8][9][10][11][12][13] but the information on the mineral structures formed was new.…”
Section: Introductionsupporting
confidence: 91%
“…This would have a significant impact on any mineral layer formed at the interface. [5] Khanna et al [7] also observed a significant change in the rate of carbon dissolution over time in some chars. Chars with high CaO levels displayed a two-stage behavior, whereby after a period of time, the rate of dissolution would decrease significantly.…”
Section: ½1mentioning
confidence: 90%
“…Following experiments that used a sessile-drop apparatus to react a drop of iron with a carbonaceous substrate, Wu et al, [19] McCarthy et al, [8][9] and Khanna et al [7] reported on the presence and composition of the ash product at the droplet/carbonaceous-material interface. General observations of the droplet surface in these studies indicate that although silica was contained in the carbonaceous material, there was none present in the ash at the interface.…”
Section: ½1mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to cost and availability constraints, it is a common practice to use carbonaceous materials such as coals, cokes, natural graphite, etc. as reductants in industrial operations [21]. Silica (up to 60%) is the main mineral impurity present in these materials.…”
Section: Introductionmentioning
confidence: 99%